## Solving the Equation (x+5)(x+5) = 49

This equation involves a squared term, making it a quadratic equation. Here's how to solve it:

### 1. Expand the equation:

(x+5)(x+5) = 49 becomes: x² + 10x + 25 = 49

### 2. Move the constant term to the left side:

x² + 10x + 25 - 49 = 0 x² + 10x - 24 = 0

### 3. Factor the quadratic equation:

The equation can be factored as: (x + 12)(x - 2) = 0

### 4. Solve for x:

For the product of two factors to be zero, at least one of them must be zero. Therefore:

- x + 12 = 0 or x - 2 = 0
- x = -12 or x = 2

### Solution:

Therefore, the solutions to the equation (x+5)(x+5) = 49 are **x = -12** and **x = 2**.